Variation patterns in the content of glycosides during green tea manufacturing by a modification-specific metabolomics approach: Enzymatic reaction promoting an increase in the glycosidically bound volatiles at the pan firing stage. (1st May 2019) - Li, Pengliang; Zhu, Yin; Lu, Meiling; Yang, Chen; Xie, Dongchao; Tan, Junfeng; Peng, Qunhua; Zhang, Yue; Ni, Dejiang; Dai, Weidong; Lin, Zhi
Highlights: A metabolomics study on the changes of glycosides during green tea manufacturing. GBVs significantly increased by 1.12–4.46-fold during pan firing. The content of GBVs was negatively related volatiles and glucose. Enzymatic reaction promotes the increase of GBVs at the pan firing stage. Abstract: The glycosides are presumed to influence the quality of green tea but the molecular mechanism behind remains unclear. To elucidate the contribution of glycosides to the flavor formation of green tea, changes of both glycosidically bound non-volatiles (GBNVs) and glycosidically bound volatiles (GBVs) during the manufacturing of green tea were investigated using a modification-specific metabolomics method. A total of 64 glycosides (47 GBNVs and 17 GBVs) were identified and their contents mainly changed during the pan firing and drying stages of green tea manufacturing. Notably, the contents of GBVs significantly increased by 1.12–4.46-fold during pan firing. Correlation analysis showed that the GBVs contents were negatively related to the contents of volatiles and glucose. Model experiments revealed that enzymatic synthesis contributed to the increase in the content of GBVs during the pan firing. This comprehensive study on the glycosides changes revealed the molecular bases for GBVs increments during the pan firing.